2017
DOI: 10.1080/15563650.2017.1353094
|View full text |Cite
|
Sign up to set email alerts
|

An internet-based survey of 96 German-speaking users of “bath salts”: frequent complications, risky sexual behavior, violence, and delinquency

Abstract: 74% of respondents were male. 41% were under the age of 30 and a further 38% between 30 and 39 years old. Cathinones were used on more than 10 days in the preceding year by 62% of study subjects. The nasal and intravenous routes of administration were most often used. About 80% of respondents reported binge use. There were frequent co-administrations of opioids and opiates. The most common complication was prolonged confusion (47%). 16% had been involuntarily confined. One third had thoughts of violence and 16… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…The changes in DAT function could be responsible, at least in part, of the psychiatric effects observed in some MDPV abusers (Schmoll et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The changes in DAT function could be responsible, at least in part, of the psychiatric effects observed in some MDPV abusers (Schmoll et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Considering the cocaine/MDMA-mixed effect molecules such as mephedrone and related compounds, mephedrone has been the most investigated. 67,68 Furthermore, Roberts et al 45 found that mexedrone, a mephedrone derivative, was found in 11 of 305 patients who presented to an emergency department (ED). All of them presented with agitation and 6 patients required sedation and/or physical restraint.…”
Section: Cathinone Categories; Clinical Peculiaritiesmentioning
confidence: 99%
“…Exposure to these NPS can be very dangerous, and intoxications were found to occur typically through inhalation or ingestion in young (20 years or older) adult males [ 78 ]. Compelling evidence has shown that the typical synthetic cathinone users are young males in their twenties and thirties, often experienced drug users, particularly of alcohol and opiates/opioids [ 118 , 119 ]. Males who attend nightclubs are also more likely to use synthetic cathinones than females [ 120 ].…”
Section: Synthetic Cathinonesmentioning
confidence: 99%